UNPACKING THE PERIL: STUDENT AWARENESS OF BANKRUPTCY RISK WITH BUY NOW, PAY LATER SERVICES - Mahmud, Nurfarizan Mazhani; Ghuslan, Mohamad Iruwan; Ahmad, Mahfuzah; Alwi, Fatimah (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
The rising popularity of Buy Now Pay Later (BNPL) services among students has introduced new financial dynamics, raising concerns about the potential risk of incurring personal bankruptcy due to unmanaged debt. Thus, this study examines university students' awareness of the risk of bankruptcy associated with using BNPL in Peninsular Malaysia. A descriptive research design was employed, using a structured questionnaire survey to gather data from a diverse student population, ranging from foundation to master's degree levels, aged between 18 and 30 years. A total of 366 valid responses were collected and analyzed. Findings reveal that most respondents are aware of the bankruptcy risk associated with BNPL, while nearly half of the respondents are aware of the bankruptcy threshold in Malaysia. However, this awareness does not necessarily translate into cautious financial behavior. Many students continue to engage in BNPL usage despite lacking stable income and financial management experience, with many displaying a tendency to spend on non-essential items driven by trends and peer influence. Alarmingly, about 50% of BNPL users reported pending payments, highlighting potential financial vulnerability at a young age. This study contributes to the growing discourse on financial literacy and responsible credit usage among youths. It provides valuable insights for policymakers, educators, and financial institutions to develop targeted awareness campaigns and early intervention strategies to prevent youth debt accumulation and potential bankruptcy.